Islamic Finance and Economic Performance: A Panel Analysis in Selected Countries - Alferez, Michelle; Bagtasos, Noel Francis; Chio, Khrystelle Shane; Payot, Justine; Laygan, Resa Mae; Abing, Martha Joy; Capulong, Charlyn; Teves, Maria Rizalia (Universitas Muhammadiyah Yogyakarta, 2024)
Financial crises, and stock markets over the years have amply shown how investors’ sentiment affect asset prices and the effectiveness of stock markets. Such a crisis brought down financial institutions sent stock markets tumbling, and left consumers scrambling due to subprime mortgages. With this, Islamic finance adoption has driven demand for Islamic financial products being free from interest. Hence, this study aimed to determine how Islamic finance can influence the economy of 19 selected countries adopting Islamic finance. These countries have marginal to significant scores in Islamic Finance across the years. This study utilized panel data from 2013 to 2021, which was gathered from the Global Islamic Finance Report, Global Innovation Report, and World Bank. A number of diagnostic tests and analyses were performed in order to reach a result that addressed the objectives and problem statement. The Panel Corrected Standard Errors analysis was used as the final model to treat heteroscedasticity, cross-sectional dependence, and autocorrelation. Based on the regression results, Islamic finance has a positive and statistically significant effect on the economy. The regression results indicate a positive and statistically significant impact of Islamic finance on the economies of the studied countries. This finding underscores the potential of Islamic finance to stimulate economic growth, enhance financial stability, and foster inclusivity in financial markets. Consequently, the findings highlight the pivotal role of macroeconomic variables and the adoption of Islamic finance principles in shaping economic outcomes.